2014
DOI: 10.1016/j.anorl.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Combined local anesthesia and monitored anesthesia care for cochlear implantation

Abstract: We find local anesthesia with light sedation a good alternative to general anesthesia for patients where general anesthesia is contraindicated. An experienced surgical and anesthesiology team is essential to shorten the duration of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Thus, patients often accept this alternative to GA. Local anaesthesia with sedation and intravenous analgesia injected under an anaesthetist's control is currently a standardised procedure that produces excellent results among co-operative adults 18 , 19 . This type of anaesthesia requires good collaboration between the surgeon and the anaesthetist, and the sedation protocol should be clearly established by the anaesthetist, with the possibility of adding dose-controlled drugs 20 . In our study, all patients underwent cochlear implantation, and no specific complications were observed.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, patients often accept this alternative to GA. Local anaesthesia with sedation and intravenous analgesia injected under an anaesthetist's control is currently a standardised procedure that produces excellent results among co-operative adults 18 , 19 . This type of anaesthesia requires good collaboration between the surgeon and the anaesthetist, and the sedation protocol should be clearly established by the anaesthetist, with the possibility of adding dose-controlled drugs 20 . In our study, all patients underwent cochlear implantation, and no specific complications were observed.…”
Section: Discussionmentioning
confidence: 82%
“…To address the needs of patients who have multiple medical problems that significantly increase the risk of GA or who harbor a fear of GA, CI surgery under local anesthesia and conscious sedation (LA‐CS) has been offered. The literature to date on CI under LA‐CS has been limited to case reports and small case series but demonstrates the feasibility of this technique 14–23 . This includes a publication from our center comparing small age‐matched cohorts of patients who underwent CI under LA‐CS and GA 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the safety and efficacy of MAC in ERCP, endoscopic ultrasound (EUS), double-balloon enteroscopy (DBE), and some ophthalmologic and otolaryngologic operations [12][13][14][15][16][17]. Berkenstadt et al performed a craniotomy under MAC in 2001 [18].…”
Section: Introductionmentioning
confidence: 97%